The political trust information: a conceptual research framework/ Akmar Hisham Mohd Yusuf@Mokhles ... [et al.] - Mohd Yusuf@Mokhles, Akmar Hisham; Wan Fakeh, Shamsul Kamal; Shahibi, Mohd Sazili; Nadzri, Zul Hisham (Faculty of Information Management, 2021)
This paper presented conceptual research framework about political trust information that affects the people's confidence towards political objects such as political system, government agencies or any policies that issued by the government. The research framework contains a few variables such as media content, quality of service and information culture that form independent variable. Meanwhile the political trust information culture values as dependent variable. The research framework has able to provide an overview and understanding on how the political trust information was established.